2021
DOI: 10.3390/biomedicines9111637
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs LY86-AS1 and VIM-AS1 Distinguish Plasma Cell Leukemia Patients from Multiple Myeloma Patients

Abstract: Long non-coding RNAs (lncRNAs) are functional RNAs longer than 200 nucleotides. Due to modern genomic techniques, the involvement of lncRNAs in tumorigenesis has been revealed; however, information concerning lncRNA interplay in multiple myeloma (MM) and plasma cell leukemia (PCL) is virtually absent. Herein, we aimed to identify the lncRNAs involved in MM to PCL progression. We investigated representative datasets of MM and PCL patients using next-generation sequencing. In total, 13 deregulated lncRNAs (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Therefore, we hypothesize that AC026355.2, despite being rarely reported, is essential for tumor growth, and further research is necessary to determine its exact function. LY86-AS1 is a lncRNA involved in the progression of multiple myeloma [ 27 ], Alzheimer’s disease [ 28 ], intracerebral hemorrhage [ 29 ], and LUAD [ 30 ]. According to our results, LY86-AS1 expression was downregulated in LUAD cells, and patients with low LY86-AS1 expression had poorer OS than high-LY86-AS1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesize that AC026355.2, despite being rarely reported, is essential for tumor growth, and further research is necessary to determine its exact function. LY86-AS1 is a lncRNA involved in the progression of multiple myeloma [ 27 ], Alzheimer’s disease [ 28 ], intracerebral hemorrhage [ 29 ], and LUAD [ 30 ]. According to our results, LY86-AS1 expression was downregulated in LUAD cells, and patients with low LY86-AS1 expression had poorer OS than high-LY86-AS1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, expression levels of 15 lncRNAs were progressively increased from NPC to PCL patients, while six lncRNAs showed a significant decrease in the transition from NPC and premalignant entities to more aggressive forms. LncRNAs involved in the progression from MM to PCL have recently been explored [39]. A total of 13 dysregulated lncRNAs was detected.…”
Section: Non-coding Rna Profilementioning
confidence: 99%
“…Beider et al indicated that transient receptor potential vanilloid 1 (TRPV1) contributed to the development of MM by disturbing calcium homeostasis and the bortezomib-induced unfolded protein response [ 9 ]. As autophagic markers, genes encoding proteins such as beclin 1 (BECLIN1) and light chain 3 (LC3) have been shown to improve the prognosis and survival of patients with MM [ 10 , 11 ]. A recent study proposed a prognostic model based on 15 autophagy-related genes that could effectively predict the prognosis of patients with MM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%